2020
DOI: 10.14324/ijdegl.12.2.02
|View full text |Cite
|
Sign up to set email alerts
|

Infusing the UN Sustainable Development Goals into a global learning initiative

Abstract: The Global Citizens Project (GCP) is a university-wide global learning initiative at the University of South Florida, aimed at enhancing undergraduate students’ global competencies through curricular and co-curricular experiences. The GCP uses the United Nations Sustainable Development Goals (SDGs) as a framework for these experiences. Understanding the SDGs allows students to expand their ideas on issues that exist in the world and how we might respond to the challenges. The purpose of this article is to prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…Sustainable development goals (SDGs) are key changes to engage in sustainable development, especially sustainable education development by citizen science, as well as holistic views proposed. Sustainable Development Goal (SDG) 4.7 focuses on the importance of learners acquiring the knowledge and skills they need to promote sustainable development and needs to be considered to be incubated to all people and continuously operationalized (Mitchell et al, 2020).…”
Section: Discussion and Final Considerationsmentioning
confidence: 99%
“…Sustainable development goals (SDGs) are key changes to engage in sustainable development, especially sustainable education development by citizen science, as well as holistic views proposed. Sustainable Development Goal (SDG) 4.7 focuses on the importance of learners acquiring the knowledge and skills they need to promote sustainable development and needs to be considered to be incubated to all people and continuously operationalized (Mitchell et al, 2020).…”
Section: Discussion and Final Considerationsmentioning
confidence: 99%
“…There seems to be a trend, however, that this is dominantly used within the higher education setting to reflect on how globalisation and internationalisation have affected the higher education curricula (Zhou 2022). For instance, in one case, researchers discuss how reflection on the UN's Sustainable Development Goals (SDGs) could enable undergraduate students to engage with global issues and develop a better understanding about our world's interconnectedness and the competencies that one should acquire in today's globalised context (Mitchell et al 2020). Nevertheless, global learning in this chapter is not understood as simply learning about the world, which focuses on skills and competencies needed in a global society, nor as a framework solely relating to global themes informing curricula design.…”
Section: Global Learning: a Pedagogy Of Interruptionmentioning
confidence: 99%
“…The current study addresses some tensions between typical characterizations of study abroad as globetrotting dilettantes rather than learners engaged in meaningful experiences towards thick and potentially critical senses of global citizenship (de Andreotti, 2014;Tiessen & Huish, 2014). Encouragingly, a recent study in which researchers analysed the content of undergraduate students' constructed responses after they engaged in global education workshops meant to supplement traditional study-abroad opportunities found evidence of increased global awareness and connections to cultural systems and issues (Mitchell et al, 2020). Kurt et al (2013) found that short-term study abroad programmes could lead to successful student outcomes in measures of global awareness, and a second study-abroad opportunity could increase the impact.…”
Section: Global Citizenshipmentioning
confidence: 99%